Carotid artery intima-media thickness correlates with oxidative stress in chronic haemodialysis patients with accelerated atherosclerosis - ÖZBEN SADIÇ, BESTE (OXFORD UNIV PRESS, 2008)
Background. Accelerated atherosclerosis is the major cause of mortality in patients on chronic haemodialysis (HD). Increased oxidative stress might be the major factor leading to high cardiovascular mortality rate in HD patients. The aim of our study was to clarify effects of uraemia and dialysis on oxidative stress parameters and explore the relation between oxidative stress markers and carotid artery intima-media thickness (CIMT) as an indicator of atherosclerosis. Methods. Twenty chronic HD patients, 20 predialytic uraemic patients and 20 healthy subjects were included in the study. Serum thiobarbituric acid reactive substances (TBARS), protein carbonyl content (PCO) and nitrite/nitrate levels were determined as oxidative stress markers. Serum vitamin E, plasma sulfhydryl (P-SH), erythrocyte glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) activities were measured as antioxidants. CIMT was assessed by carotid artery ultrasonography. Results. Both chronic HD and predialytic uraemic patients had enhanced oxidative stress indicated by higher levels of nitrite/nitrate, TBARS and PCO, and lower levels of P-SH, SOD, CAT and GPx compared to controls. HD patients had significantly higher CIMT and nitrite/nitrate while significantly lower P-SH,vitamin E, SOD, CAT and GPx compared to predialytic uraemic patients. There was a significant positive correlation between CIMT and TBARS (r = 0.38, P= 0.003) and nitrite/nitrate levels (r= 0.41, P= 0.001), while there was a significant negative correlation between CIMT and SOD (r= -0.35, P= 0.01), CAT (r= -0.65, P < 0.001) and P-SH levels (r= -0.50, P < 0.001). A linear regression analysis showed that TBARS were still significantly and positively correlated with CIMT (P= 0.001), while CAT and P-SH were significantly and negatively correlated with CIMT (P= 0.002 and P= 0.048, respectively). Conclusions. HD exacerbates oxidative stress and disturbances in antioxidant enzymes in uraemic patients. We propose that serum TBARS and nitrite/nitrate can be used as positive determinants, while erythrocyte SOD, CAT and P-SH may be used as negative determinants of atherosclerosis assessed by CIMT in uraemic and HD patients.
Keywords: carotid artery intima media thickness; chronic haemodialysis patients; oxidative stress; CHRONIC-RENAL-FAILURE; CARDIOVASCULAR RISK-FACTORS; ACETATE-FREE BIOFILTRATION; NITRIC-OXIDE PRODUCTION; MYOCARDIAL-INFARCTION; DIALYSIS HYPOTENSION; DIABETES-MELLITUS; WALL THICKNESS; TNF-ALPHA; DISEASE